Tinjauan Hukum Tentang Penetapan Wali Adhal Menurut Hukum Perkawinan (Studi tentang Penetapan Nomor 005/Pdt.P/2012/PA.Skh) - Ayuningtyas, Mutiara Mei, Mutimatun Ni'ami, SH,M.Hum, Ahmad Ridho,SH (2015)
This study aims to determine the legal basis and procedures for the determination of states allow surrogate guardian when the guardian has the right to marry declared adhal/reluctant and legal consequences of the determination of trustees adhal/reluctant. The research method using normative legal research or descriptive doctrinal study. Methods of data analysis using interactive analysis model, which is a process of analysis by using three components consisting of data reduction, data presentation, and then concluding that shape interactive activity is a cyclical process. Based on the research results we concluded that the procedures for the determination of a replacement trustee to trustee adhal carried out in the trial that includes the calling parties litigant by a religious court, the peace efforts by the judges, the reading of a letter of application, examination proceedings, and the reading of the result of the determination of the panel of judges. Determination adhal guardian / ward's reluctant result moved or replaced by Wali Hakim is head of the Religious Affairs Office of the District Registrar of Marriage and Employee as if unable replaced Section Head of Islamic Affairs on behalf of the Head of the Religious Affairs Office of the District / Municipality.